Chimeric design, synthesis, and biological assays of a new nonpeptide insulin-mimetic vanadium compound to inhibit protein tyrosine phosphatase 1B - Thomas, Scior; José Antonio, Guevara García; FJ, Melendez; H Abdallah, Hassan; Do, Quoc Tuan; Philippe, Bernard (Dove Medical Press, 2010)
Prior to its total synthesis, a new vanadium coordination compound, called TSAG0101, was computationally designed to inhibit the enzyme protein tyrosine phosphatase 1B (PTP1B). The PTP1B acts as a negative regulator of insulin signaling by blocking the active site where phosphate hydrolysis of the insulin receptor takes place. TSAG001, [VVO2(OH)(picolinamide)], was characterized by infrared (IR) and nuclear magnetic resonance (NMR) spectroscopy; IR: ν/cm−1 3,570 (NH), 1,627 (C=O, coordinated), 1,417 (C−N), 970/842 (O=V=O), 727 δ. (pyridine ring); 13C NMR: 5 bands between 122 and 151 ppm and carbonyl C shifted to 180 ppm; and 1H NMR: 4 broad bands from 7.6 to 8.2 ppm and NH2 shifted to 8.8 ppm. In aqueous solution, in presence or absence of sodium citrate as a biologically relevant and ubiquitous chelator, TSAG0101 undergoes neither ligand exchange nor reduction of its central vanadium atom during 24 hours. TSAG0101 shows blood glucose lowering effects in rats but it produced no alteration of basal- or glucose-induced insulin secretion on β cells during in vitro tests, all of which excludes a direct mechanism evidencing the extrapancreatic nature of its activity. The lethal dose (LD50) of TSAG0101 was determined in Wistar mice yielding a value of 412 mg/kg. This value is one of the highest among vanadium compounds and classifies it as a mild toxicity agent when compared with literature data. Due to its nonsubstituted, small-sized scaffold design, its remarkable complex stability, and low toxicity; TSAG0101 should be considered as an innovative insulin-mimetic principle with promising properties and, therefore, could become a new lead compound for potential nonpeptide PTP1B inhibitors in antidiabetic drug research. In view of the present work, the inhibitory concentration (IC50) and extended solution stability will be tested.